El modelo costo-volumen-utilidad y su incidencia en la planeación de utilidades de la empresa "Academia Miguel Grau" del distrito de Casa Grande, año 2017 - Gonzales Chamay, Segundo Felipe (2017)
Companies want to get profits to expand, but not all of them because owners are unaware of management tools, they do not plan for profits, and therefore cause them to ignore their true profit, assuming that everything is going well in their company because of the presence of cash; also causes that when changes occur in their sales and costs do not know to face them and soon disappear. This research aims to demonstrate that Cost-Volume-Utility allows the company Miguel Grau Academy dedicated to the provision of educational services of preuniversity preparation, to maintain the utility planned against any change in sales volume, sale price, its fixed costs and variable costs. When starting the analysis of the situation of the company, it was determined that the Miguel Grau Academy, does not have a correct control of their income and costs, did not classify their costs in fixed and variable, does not know exactly the unit cost of each educational service, and for the determination of the selling price are based on experience, in addition, the break-even point is not determined, nor does it plan its profits. In view of the problems encountered, it is suggested that the Miguel Grau Academy determine the unit cost of each of its services offered, since this information will serve to calculate the sales price of each educational service and undertake the planning of its services. utilities. It is also recommended that in the process of determining the cost of your services, the company discriminates its costs in fixed and variable, this will make it easier to calculate the breakeven point where you do not win or lose. On the other hand, the company must consider in each academic cycle, the calculation of the break-even point, since, with this will begin the planning of its profits. Finally, it is advised that the Miguel Grau Academy must incorporate within its corporate culture the use of the Cost-Volume-Utility model since, with the help of this, the company will achieve that the planned utility does not change despite any changes.